How can Digital Tourism Big Data Analysis Unlock Untapped Tourism Potential? - Lawelai, Herman; Sadat, Anwar; Suherman, Ansar; Alfinta, Muhammat Alim; Ishaq, L.M. Ahsan (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research delves into the realm of digital tourism, aiming to unlock untapped potential through the analysis of big data. Utilizing Brand24.com, the study collects extensive data on traveler trends, preferences, and location ratings sourced from various digital channels, including tourism websites, social media platforms, and travel forums. Employing advanced keyword search and monitoring capabilities, the data undergoes rigorous qualitative and quantitative analysis to discern emerging patterns and sentiments. The primary objective lies in the identification of potential tourism development opportunities within the Buton Islands. By scrutinizing growth potential, desirability, and socio-economic impact, strategic decisions are formulated to cultivate a focused tourism strategy. This strategy not only aims at fostering economic growth but also prioritizes environmental sustainability. The significance of this study lies in its emphasis on the pivotal role of big data in deciphering and anticipating trends in the dynamic tourism sector. Through comprehensive analysis, the research seeks to provide actionable insights for stakeholders to capitalize on burgeoning tourism opportunities effectively. By bridging the gap between traditional tourism practices and contemporary data-driven insights, this research offers a pioneering approach to destination management. It advocates for the integration of digital tourism big data analysis as a cornerstone of strategic decision-making processes within the tourism industry. In conclusion, this study underscores the transformative potential of digital tourism big data analysis in unlocking hitherto unexplored avenues for tourism development. It serves as a beacon for future research endeavors and practical implementations aimed at harnessing the power of big data to propel sustainable tourism growth.